Reliability Evaluation for LTE Based CBTC Train Ground Communication Systems - Shuo Wang; Li Zhu; Kun Xu; Lin Zhang; Xuan Wang (Journal of Advanced Transportation)
Nowadays, most communication based train control systems (CBTC) use Wireless Local Networks (WLAN) technology for information transmission. However, because of the high running speed of the train in urban rail transit, WLAN technology cannot fully satisfy the information transmission under the condition of train operation at a high speed. Long term evolution (LTE) technology has a high transmission speed, which can better meet the real-time requirements of train and ground information transmission. Therefore, LTE technology has become an emphasis on the research of communication technology in today’s urban rail transit. Although there is a lot of research on the application of LTE technology in urban rail transit, there is little research on the reliability of LTE based train ground communication systems using experimental data. In this paper, the reliability of train ground communication is firstly defined. Then the train ground communication environment was established in the laboratory, and the performance parameters of train ground communication based on LTE technology were obtained in the test. Finally, the reliability is calculated and analyzed according to the experimental results, and a storage method of train data in actual operation is proposed, which can be used to analyze the reliability of train information transmission. The results show that the reliability of train ground communication based on LTE technology meets CBTC requirements.